2010
DOI: 10.1098/rstb.2009.0313
|View full text |Cite
|
Sign up to set email alerts
|

Glial cells in neuronal network function

Abstract: Numerous evidence demonstrates that astrocytes, a type of glial cell, are integral functional elements of the synapses, responding to neuronal activity and regulating synaptic transmission and plasticity. Consequently, they are actively involved in the processing, transfer and storage of information by the nervous system, which challenges the accepted paradigm that brain function results exclusively from neuronal network activity, and suggests that nervous system function actually arises from the activity of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
205
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(216 citation statements)
references
References 59 publications
1
205
0
10
Order By: Relevance
“…This supported by the finding of [27] they cleared the role of glia and astrocytes in the activity of the neuronal networks. They showed that the microglia are activated in many neurodegentative diseases, adding that whether they are helpful or harmful.…”
Section: Discussionsupporting
confidence: 70%
“…This supported by the finding of [27] they cleared the role of glia and astrocytes in the activity of the neuronal networks. They showed that the microglia are activated in many neurodegentative diseases, adding that whether they are helpful or harmful.…”
Section: Discussionsupporting
confidence: 70%
“…However, it should be noted that the concentrations of Glu and GABA, as neurotransmitters, are determined not only by their biosynthesis but also by their terminal release and uptake (45). The glial cells and the process of myelination may also change with age and influence the intracellular levels of transmitters (46,47). Therefore, further study of relationship between age and the GlnGlu-GABA biosynthetic pathway is needed.…”
Section: Discussionmentioning
confidence: 99%
“…На современном этапе большинство авторов рассматри-вают информационный процессинг в мозге как функцию нейроглиальных сетей. Как сформулировали A. Araque и M. Navarrete [14], в этом случае используется как бинар-ное (потенциал действия нейронов), так и аналоговое (диффузное распространение медиаторов через контакты между астроцитами или через межклеточные простран-ства) кодирование сигнала.…”
Section: роль астроцитов в глутаматергической нейромедиацииunclassified
“…Кальциевые волны распростра-няются на соседние астроциты благодаря связывающим их контактам указанного выше типа. Повышение концен-трации ионов кальция в астроцитах стимулирует в свою очередь высвобождение из них активных веществ -так называемых глиотрансмиттеров -таких как глутамат, D-серин и другие эндогенные лиганды рецепторов глута-мата, способные воздействовать на возбудимость нейро-нов и синаптическую передачу [14,17].…”
Section: роль астроцитов в глутаматергической нейромедиацииunclassified